The Relation between Mentalized Affectivity and Negative Emotions in Chinese College Students: The Moderating Effect of Internet Altruistic Behavior - Zhang, Qing (Science Insights Education Frontiers, 2024)
This article aims to investigate the impact of mentalized affectivity on negative emotions among Chinese college students based on a questionnaire survey of 899 university students. The study adopts a mentalized affectivity scale, an internet altruistic behavior scale, and a self-analysis questionnaire. The study’s findings reveal a negative correlation between mentalized affectivity and depression, anxiety, and stress, but a positive correlation with variables linked to internet altruistic behavior in college students. Additionally, the study reveals a significant moderating effect of internet altruistic behavior on the relationship between mentalized affectivity and depression and anxiety. It is concluded that an increased level of affectivity can help modulate negative emotions and that internet altruistic behavior can play a moderator role in the modulation process.